2008
DOI: 10.1586/14737159.8.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of stroke: a review of recent advances

Abstract: Stroke is a multifactorial disease responsible for nearly 10% of deaths each year in industrialized countries. While some monogenic forms of stroke have been described, the vast majority result from the common polygenic form of the disease. Progress in molecular genetics has allowed the identification, through genome-wide linkage analysis, of various candidate genes, including the genes encoding PDE4D and ALOX5AP. Since then, genetic research has been extensively performed from single candidate genes to whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 149 publications
1
27
0
Order By: Relevance
“…Boxes surrounding SNP names indicate the 12 polymorphisms that we Wrst genotyped virtually all tissues, while nNOS and eNOS are constitutively expressed primarily in neural tissue and endothelium, respectively, which are the principal tissues involved in stroke. Several published case-control studies describe an association of genetic variants in eNOs with ischemic stroke risk (Domingues-Montanari et al 2008), and we have found an association of nNOS with IS (personal communication). Kalirin-7 is involved in the regulation of ischemic signal transduction (Beresewicz et al 2008), and may play a neuroprotective role during inXammation of the central nervous system by inhibiting iNOS activity (Ratovitski et al 1999).…”
Section: Discussionsupporting
confidence: 52%
“…Boxes surrounding SNP names indicate the 12 polymorphisms that we Wrst genotyped virtually all tissues, while nNOS and eNOS are constitutively expressed primarily in neural tissue and endothelium, respectively, which are the principal tissues involved in stroke. Several published case-control studies describe an association of genetic variants in eNOs with ischemic stroke risk (Domingues-Montanari et al 2008), and we have found an association of nNOS with IS (personal communication). Kalirin-7 is involved in the regulation of ischemic signal transduction (Beresewicz et al 2008), and may play a neuroprotective role during inXammation of the central nervous system by inhibiting iNOS activity (Ratovitski et al 1999).…”
Section: Discussionsupporting
confidence: 52%
“…Hypertension, diabetes mellitus, and dyslipidemia have been demonstrated by others to be related to cerebral infarction, and are recognized as traditional risk factors (Park et al, 2014). Genetics and molecular biology studies have revealed the existence of genetic predisposition to cerebral infarction, and have identified various polymorphisms associated with this condition (Domingues-Montanari et al, 2008;Xu et al, 2008). Atherosclerosis, the inflammatory response, and impaired vascular endothelial function play an important role in the development of cerebral infarction (Pucci et al, 2011;Soskić et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The 2 test was used to analyze the deviation of Hardy -Weinberg equilibrium for genotype frequencies. Continuous variables were compared between patients with IS and controls using the Student's t -test.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a leading cause of mortality and disability [1][2][3] . Ischemic stroke (IS) is the most common type, accounting for up to 80% of all strokes 4) .…”
Section: Introductionmentioning
confidence: 99%